Physical and mechanical properties of foam-type panels manufactured from recycled cardboard - Mazaherifar, Mohammad Hassan; Coşereanu, Camelia; Timar, Cristina Maria; Georgescu, Sergiu-Valeriu (Elsevier BV, 2024)
This study investigated different properties of foam-type composites made from recycled cardboard. Two types of panels, type A (237.36 kg/m3) and type B (284.28 kg/m3) were manufactured varying the share of corn starch as binder. Dimensional stability to water, vertical density profile (VDP), thermal conductivity, bending charac-teristics, and internal bond strength tests were conducted. The results revealed that the higher corn starch content improved the modulus of elasticity (MOE), modulus of rupture (MOR), and internal bond strength (IB) by 56%, 33%, and 30% for panel type B, respectively. However, no significant difference was observed for the internal bonding strength test. Statistical analysis revealed that no substantial difference in the thermal con-ductivity property of the two types of panels was determined at a 95% confidence level. The water absorption and thickness swelling increased for both samples after 24 h water immersion. Foam-type panels made from waste cardboard would have the potential to be used for certain applications such as insulation purposes within the perspective of sustainability and a green approach.
Keywords: Recycled cardboard; Foam composites; Physical properties; Mechanical properties; FTIR\; Microscopy